"We've Got to Keep Meeting Like This": A Pilot Study Comparing Academic Performance in Shifting-Membership Cooperative Groups Versus Stable-Membership Cooperative Groups in an Introductory-Level Lab. Issue 1 (2nd January 2017) - Walker, Alicia; Bush, Amy; Sanchagrin, Ken; Holland, Jonathon
ABSTRACT: This study examined possible ways to increase student engagement in small sections of a large, introductory-level, required university course. Research shows that cooperative group learning boosts achievement through fostering better interpersonal relationships between students. Cooperative group learning is an evidence-based instructional practice engaging students in active learning. The present study investigated whether cooperative groups with sustained-membership functioned more effectively for boosting performance than shifting-membership cooperative groups. Findings indicated that the amount of class time spent in groups influenced the impact of shifting or sustained-membership. A significant difference in performance was found for sustained-group students when group activities were used the majority of the time during recitation.